Peran Kolaboratif Konselor di Sekolah Inklusif - Redita Yuliawanti (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
Strengthening Inclusive Education requires the role of various parties in educational institutions including guidance and counseling. Guidance and counseling services at the Inclusive Schools currently oriented towards developmental guidance and counseling with targeted services not limited to normal students in institutional settings, but will be directed to all students in various life and cultural settings including their special needs. Inclusive education is a shared responsibility between school Counselor, Teacher, Special Assistant teacher (GPK), and also Parents. Teachers cannot do everything themselves, because parents need to be involved so that the implementation of activities in school continues with the activities of students at home. Collaboration forms the basis between school and parents, as well as other experts, to provide assistance in a systematic, programmed, consistent and ongoing manner. Thus, the collaborative role of the counselors is needed, the development of the counselor's skills, and the professional implementation of the guidance and counseling program to optimize the development of students with special needs in inclusive schools. Collaboration for student success is an integral part of educational reform in inclusive schools